Dean Banta Album,
One photo album of orchards, homes and the paper plant in Millwood, Washington. Many photographs of one extensive home owned by the Frank N. Walker family. Photographs include interior shots as well as pictures of the orchard. Other photographs show orchards in the area and other homes. The photographs were mounted on linen and placed in a leather binder. Two photographs show the Spokane Portland Cement Company (originally the International Portland Cement Company Ltd.).